ICT LITERACY IN RURAL COMMUNITIES IN THE ERA OF GLOBALIZATION - Dini Haryati Haryati; Yudha Ginanjar (SEAN Institute, 2020)
The development of information and communication technology is one form of the presence of the era of globalization. The faster the development, the easier it is for someone to access information. However, the inequality of technological developments can be felt in places where internet access is difficult, such as in Ciakar Village. With descriptive quantitative research, this research can see the views of the Ciakar Village community in facing the development of information and communication technology. The development of ICT is currently needed not only in cities but also in villages, because ICT literacy provides many benefits both in the economic, social, cultural, political and so on. So that the development of this ICT